Respon Masyarakat terhadap Fenomena "Childfree" (Studi Kasus influencer Gita Savitri) - Intan Leliana; Ita Suryani; Achmad Haikal; Rio Septian (Cakrawala - Jurnal Humaniora, 2023)
This study aims to describe the public's response to the Childfree phenomenon which has recently become a trend due to influencer Gita Savitri's comments. Childfree itself is used for someone who does not want to have children. This lifestyle is inversely proportional to the pattern that occurs in Indonesia. Where religious and customary factors in Indonesia strongly recommend having children even if only one. This study used a qualitative approach with phenomenological type. The results obtained that the community provides responses in the form of cognitive, affective and behavioral which are divided into two perspectives, namely socio-cultural and religious perspectives. The response of society when viewed from a socio-cultural perspective that the status and existence of women in the past was seen from how many children she could bear children, and the pattern that occurred in Indonesia for married couples to have children even if only one. Then if viewed from a religious perspective that having offspring is a recommendation in Islam is not an obligation. So that childfree is not included in the category of prohibited acts, because every married couple has the right to plan and manage their home life including having children. Keywords: Phenomenon, childfree, Community response